Ultrastructure on the light organ of tropical synchronize firefly, Pteroptyx tener - Nur Khairunnisa Salleh,; Nurul Wahida Othman,; Norela Sulaiman,; Ismail Sahid, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The ultrastructure of the light organ Pteroptyx tener was examined using a Carl Zeiss Axioscope microscope and transmission electron microscope (TEM). The light organ of the male and female P. tener comprises of two layers namely the photogenic layer and the dorsal (reflector) layer. Photogenic layer consists of several elements, i.e. photocyte, differentiated zone, cylinder, trachea and trachea end cell. The photocyte is the main source of the emitted light. This layer is packed with photocyte granules except at a differentiated zone that have low granules but high number of mitochondria. The reflector layer comprised of trachea and the cytoplasm of the cells in this layer is densely packed with spherical uric acid granule. The finding of this study has shown that P. tener have similar general histology structure of light organ of fireflies species that produce sharp flashes. However, the cylinder and trachea end cell may have significant capacities in controlling the luminescent creation in the fireflies that need to be investigate further.